Nanostructure of pseudomonocrystalline graphite studied by nanoimaging of electrical properties in combination with other techniques. (April 2017) - Shumilova, T.G.; Golubev, Ye.A.; Mayer, J.; Shevchuk, S.S.; Radaev, V.A.; Isaenko, S.I.; Tkachev, S.N.
Abstract: A complex approach, which includes simultaneous data acquisition and processing, to analyze various physical parameters characteristics of the same sample cross-section at high resolution allows to extract information of much better quality and, thus, is a basis of modern studies at nanolevel. A concomitant investigation of surface topography and local electrical features of presumably defect-laden pseudomonocrystalline graphite is presented as an example. The structural state of graphite is monitored "in situ" using the microdiffraction unit of scanning electron microscope VEGA3 TESCAN and additionally tested by high resolution Raman spectroscopy measurements. The study reveals a previously undetectable by standard nanotopographic and X-ray diffraction observations nanostructure of pseudomonocrystalline graphite. A novel graphite-carbyne intergrowth model based on the energetically stable attachment of carbyne-like CC bonded chains to sp 2 graphitic fragments is presented. Graphical abstract: